Seblak sebagai Comfort Food dan Identitas Budaya Generasi Z: Sebuah Pendekatan Fenomenologi - Rostika Yuliani; Lu’lu Mutia; Xaverius Alberto Lartutul; Sa’adatul Aliyah; Mariani (Universitas Negeri Medan, 2025)
Seblak, a typical Sundanese snack made from wet crackers with a spicy taste, has now become part of popular culture favored by Generation Z. Although many previous studies have examined seblak from culinary, economic, and product promotion perspectives, studies that highlight the social meaning, cultural identity, and gender dimensions in seblak consumption are relatively limited. This study aims to explore the meaning of seblak consumption among Generation Z using Alfred Schutz's phenomenological approach. Data were obtained through in-depth interviews with eight informants in Bandung City who were selected purposively. The results show that seblak is not only interpreted as spicy and inexpensive food, but also as comfort food that functions as a stress reliever, a means of strengthening social interaction, and a symbol of Sundanese cultural identity. Furthermore, a gender dimension also emerged, where seblak consumption by men is often associated with shifts in masculinity. This research contributes to the enrichment of cultural communication studies and food studies, particularly regarding how Generation Z constructs meanings about traditional foods in the era of social media.